2010
DOI: 10.1089/acm.2009.0355
|View full text |Cite
|
Sign up to set email alerts
|

Brief Effect of Acupuncture on the Peripheral Arterial System of the Upper Limb and Systemic Hemodynamics in Humans

Abstract: The present study showed that radial and brachial artery blood flow volume decreased immediately during acupuncture on LR-3 acupoint, but increased at 180 seconds after acupuncture. This reaction is attributed to the change in peripheral vascular resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
27
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 29 publications
6
27
1
Order By: Relevance
“…Doppler ultrasound has been used clinically for noninvasive assessment of the SMA hemodynamics. We have already reported the changes of blood flow volume in the SMA and brachial artery due to abdominal thermal stimulation and the effect of acupuncture on radial artery blood flow volume by ultrasound [16][17][18]. These reports suggested the efficacy of ultrasound for assessing the blood flow change in the various organs treated by traditional medicine.…”
Section: Introductionmentioning
confidence: 93%
“…Doppler ultrasound has been used clinically for noninvasive assessment of the SMA hemodynamics. We have already reported the changes of blood flow volume in the SMA and brachial artery due to abdominal thermal stimulation and the effect of acupuncture on radial artery blood flow volume by ultrasound [16][17][18]. These reports suggested the efficacy of ultrasound for assessing the blood flow change in the various organs treated by traditional medicine.…”
Section: Introductionmentioning
confidence: 93%
“…Pulsed Doppler ultrasound has been used clinically for noninvasive assessment of SMA hemodynamics. We have already reported on blood flow volume changes in the SMA and brachial artery in response to abdominal thermal stimulation as well as changes in radial artery blood flow volume in response to acupuncture, as determined by ultrasound (Takayama 2009a(Takayama , 2009b(Takayama , 2009c. These reports suggest that ultrasound is effective for assessing the hemodynamic effects of traditional medicines.…”
mentioning
confidence: 90%
“…Therefore, scientific elucidation of underlying acupuncture mechanism is essential for the therapy to be generally accepted in the future. There are only few studies in which quantitative measurement of blood flow in response to stimulation of a specific acupoint was conducted at clinical sites11, 12, 13; whereas, numerous studies were conducted on hemodynamic change following acupuncture therapy. Takayama et al 11 measured blood pressure (BP), cardiac index (CI) and systemic vascular resistance index (SVRI), and the diameter and blood flow volume of left brachial and radial arteries in response to acupuncture therapy applied to Taichong (LR-3), focusing on the effect of the stimulation of the acupoint on the hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…There are only few studies in which quantitative measurement of blood flow in response to stimulation of a specific acupoint was conducted at clinical sites11, 12, 13; whereas, numerous studies were conducted on hemodynamic change following acupuncture therapy. Takayama et al 11 measured blood pressure (BP), cardiac index (CI) and systemic vascular resistance index (SVRI), and the diameter and blood flow volume of left brachial and radial arteries in response to acupuncture therapy applied to Taichong (LR-3), focusing on the effect of the stimulation of the acupoint on the hemodynamics. The authors of that study demonstrated that blood flow volume in the arm decreased during twisting of the acupuncture needle and then increased to a level higher than the preacupuncture level at 180 seconds after the stimulation, while BP and CI were not changed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation